KINERJA PERUSAHAAN SEBAGAI DAMPAK DARI CORPORATE GOVERNANCE DAN KONSERVATISME AKUNTANSI (STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX) - Setiawan; Hendi Rohendi (LPPM POLITEKNIK LP3I BANDUNG, 2016)
In 2012, the average of Return on Assets (ROA) in companies listed on the Jakarta Islamic Index have significant decrease in the 5 (five) years. Suspected factors influencing the decline are Corporate Governance and Accounting Conservatism. This study sought to examine the effect of the Corporate Governance and Accounting Conservatism on Return on Assets. The research used company data who listed in Jakarta Islamic Index and include CGPI (Corporate Governance Perception Index) score in 2008, 2009, 2010, 2011, and 2012. Sample gathered by purposive sampling method and give 29 companies for year 2008-2012. This secondary data analyzed by using simple regression model. Regression analysis showed that R2 reaches 0.038. It shows that only 3.80 percent return on assets variables can be explained by the Corporate Governance and Accounting Conservatism. Meanwhile, according to the results obtained path analysis calculations show that the indirect effect of only 0.003764, or approximately 0.38%. Conclusion The results of the study are as follows: (i) Corporate Governance have no significant influence on Return on Assets; (ii) Accounting Conservatism have no significant influence on Return on Assets; (iii) Corporate Governance and Accounting Conservatism have no significant influence on Return on Assets